WAYS TO USE THE SEVEN PIR INSTRUCTIONS OF ABDUHOLIK GIJDUVANI IN THE EDUCATION OF MANAWY HARMONIOUS YOUTH (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article covers the works of Abdulkholik Gijduvani on spiritual heritage,decency,the achamity of the seven pir teachings in human perfection. The content of the formation of social activity on the basis of the formation of base competencies in students, the ability to eliminate conflicts and problems arising as a component of social activity to promote students to occupy a worthy place in the microsocium in the future, important components of social activity that are not always manifested in the activities of students, but